ИННОВАЦИОННЫЕ АРХИТЕКТУРНО ПЛАНИРОВОЧНЫЕ РЕШЕНИЯ ТРАНСПОРТНО ПЕРЕСАДОЧНЫХ УЗЛОВ В ГОРОДЕ ТАШКЕНТЕ. (KIUT Publication, 2025)
The article is devoted to the study of innovative architectural and planning solutions for transport hubs in the city of Tashkent. In the context of growing urbanization and increasing traffic flows, the importance of developing efficient and convenient transport hubs is becoming especially relevant. The work analyzes modern trends in the design of such facilities, taking into account the specifics of the urban landscape, cultural and climatic features, as well as the needs of the population. Examples of innovative technologies, such as the integration of various modes of transport, the use of smart traffic management systems and environmentally friendly materials are considered. Particular attention is paid to improving passenger comfort and optimizing transport routes. In conclusion, recommendations are offered for improving existing transport hubs in Tashkent, aimed at improving their functionality and reducing the load on the urban infrastructure.